A viabilidade do Registro da Indicação Geográfica (IG) "Lagoa da Confusão-TO" para as sementes de feijão - MONTEIRO, Mavine Pereira Barbosa (2011)
This thesis assumes that the externalities caused by lack of information about the safety of our food are caused mostly by lack of information, which characterizes a market failure, in which the latter cannot coordinate integration between the various players in this market, as producers and consumers, exporters and importers, what economists call the information asymmetry. Lack of information increases transaction costs, since consumers do not have access to perfect information about the products they consume, with damage costs will have to investigate the origin of the food they are buying. This theory also applies to the costs of informational asymmetry that producers face, since they also need to know about the origin and quality of inputs they use in production, so that the product certification and seed emerges as a solution to the problem of information asymmetry. According to the theoretical framework of New Institutional Economics, contracts assist in the reduction of transaction costs in the operation of an economy, and the informational asymmetry is one of these transaction costs, which causes a market failure. For this study we analyzed the possible certification as an inhibitor of such asymmetric information, since this is also a contract that the producers of some good firm with a public or private institution with a commitment to meet pre-established norms and that the information on the origin, quality, validity and other important features are exposed in the certification seal of the product, inspiring confidence for potential buyers of the product and possibly raising the value-added product. For this study examined the case of a possible certification of geographical indication for the bean seeds produced by an association of producers in the floodplains of river Javaés, arm of the Araguaia River, in the municipality of Lagoa Confusion in the state of Tocantins, where he addressed the potential economic benefits for producers and local economy of the region and the sustainability and environmental impacts that the intensive cultivation in tropical wetlands can cause to the ecosystem of that region.